Attachment Security and Attachment Styles in Romantic Relationships - Zahra , Fatima Tu (South Asian Journal of Social Sciences and Humanities, 2022)
Purpose. The present research aimed at studying the Attachment Security, Attachment Styles in  Romantic Relationships.  Method. Cross sectional research design was used in this study. The sample (N = 148) was selected  via online poll due to COVID regulations. Non probability purposive sampling technique was used  to collect sample. The Ainsworth Security Questionnaire Revisited ASQ- R was used to study  attachment security in early childhood and Experiences in close relationships Revised ECR-R  Scale was used in this study to evaluate attachment styles in romantic relationships.  Results. Results showed that attachment security was negatively correlated with insecure  attachment styles. It was also proved that those who scored low on attachment security measure  scored high on either anxious attachment dimension or avoidant attachment dimension.  Novelty/Originality of The Study. The main goals of this study were to develop a warm  collaborative therapy connection, identify particular problem sets and associated goals, psycho educate the participants.  Implications. The study will help how psychotherapy can help those with unhealthy attachment  styles to heal and have relationship satisfaction in romantic relationships by identification of  insecure attachment styles.
Keywords: Attachment security; attachment styles; adults in romantic relationships